Neuroprotective Effects of Castanea sativa Mill. Bark Extract in Human Neuroblastoma Cells Subjected to Oxidative Stress. Issue 2 (3rd September 2015) - Brizi, Claudia; Santulli, Chiara; Micucci, Matteo; Budriesi, Roberta; Chiarini, Alberto; Aldinucci, Carlo; Frosini, Maria
ABSTRACT: One of the major features of neurodegenerative disease is the selective vulnerability of different neuronal populations that are affected in a progressive and often stereotyped manner. Despite the susceptible neuronal population varies between diseases, oxidative stress is implicated as the major pathogenic process in all of them. Natural Extract of Castanea sativa Mill . bark (ENC), recently characterized in its phenolic composition, acts as antioxidant and cardioprotective agent. Its neuroprotettive properties, however, have never been investigated. The aim of this study was to assess neuroprotection of ENC in in vitro models of oxidative‐stress‐mediate injury. Human neuroblastoma SH‐SY5Y cells treated with glutamate (50 mM for 24 h) or hydrogen peroxide (25 μM for 1 h followed by 24 with medium) were used. The results showed that the addition of ENC (1–50 μg/ml) to cell medium before the neuronal damage provided neuroprotection in both experimental models used, while its addition after the injury was ineffective. In conclusion, the present results suggest that ENC could be a valuable support as dietary supplement, combining beneficial preventive neuroprotettive effects with a high antioxidant activity. J. Cell. Biochem. 117: 510–520, 2016. © 2015 Wiley Periodicals, Inc.